Pharmacometrics and Systems Pharmacology 2030. Issue 1 (23rd November 2019) - Mentré, France; Friberg, Lena E.; Duffull, Stephen; French, Jonathan; Lauffenburger, Douglas A.; Li, Lang; Mager, Donald E.; Sinha, Vikram; Sobie, Eric; Zhao, Ping
Abstract : In 2012, a new journal was launched from the ASCPT family, CPT: Pharmacometrics and Systems Pharmacology ( PSP ) as both quantitative system pharmacology (QSP) and pharmacometrics were growing fields in pharmacology, drug development, and drug use. In this Perspective, the present editors and associate editors of PSP want to share their strategic vision of where these two fields, separately and together, should, would, or could be 10 years from now.